Electronic properties of one-dimensional pentacene crystals. (7th October 2020) - Nappi, C; Romeo, F; Sarnelli, E
Abstract: The electronic properties of an infinite row of freestanding, aligned side-by-side, pentacene molecules are derived as a function of the intermolecular overlap integral and the chemical potential shift. We use a semiclassical approximation and a first principles tight binding method to obtain conductance and mobility of this one-dimensional crystal as a function of temperature and gate voltage. For two values of the intermolecular overlap, energy bands show a metallic behavior. For all the other values, a bandgap is present and evolves with the intermolecular overlap following a typical modulation. The magnitude of the scattering parameters estimated by the observed conductivity is coherent with the existing literature values. These findings could be relevant for the implementation of organic-based sensors.